Profitability of Islamic Commercial Banks in Indonesia: Wadiah Savings and Wadiah Demand Deposits - Mochammad Ainur Rozikin; Guntur Kusuma Wardana; Noer Aisyah Barlian (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2025)
Banks are considered to be able to manage their operations well in the event of an increase in profit (profitability). Profitability is an important aspect that needs to be analyzed because it serves as an indicator of the bank's success in carrying out the role of intermediation of public funds. Therefore, Islamic banks need to increase their profitability. Factors such as wadiah savings, wadiah current accounts, are considered to be able to contribute to a sustainable increase in profitability, because they reflect the bank's ability to manage financial risks, fulfill obligations, and optimize the use of its assets. The purpose of the study was to determine the effect of wadiah savings and wadiah current account on profitability with profit-sharing financing and non-profit-sharing financing as control variables. The research method used is quantitative with a descriptive approach. The population of 14 sharia commercial banks in Indonesia will be registered with the OJK in 2024, with purposive sampling techniques obtained by 8 sharia commercial banks as samples. The data used is secondary data taken from financial statements on the official website of each Islamic commercial bank during the 2013-2024 period. The analysis was carried out using the panel data method and using Eviews 13. He results show that wadiah savings, wadiah savings partially affect the profitability of Islamic commercial banks in Indonesia. Simultaneously, wadiah savings and wadiah current accounts affect the profitability of Islamic commercial banks in Indonesia.